STRATEGI PEMERINTAH KABUPATEN BANYUWANGI DALAM MENINGKATKAN INDUSTRI PARIWISATA MELALUI USAHA MIKRO KECIL MENENGAH (UMKM) - Dimas Imaniar; Andhika Wahyudiono (Universitas Tribhuwana Tunggadewi, 2019)
Banyuwangi Regency's economy shows a positive trend which is realized in the form of creative economic innovation supported by innovation in the field of tourism based on local wisdom. This causes an increase in population income with a projected Economic Growth (PE) of 6.57 percent in 2018. The government achievement target is to maintain public consumption and encourage the effectiveness of regional spending. The descriptive qualitative research method aims to obtain a description (description) of the role of MSMEs in developing the welfare of rural communities in Banyuwangi Regency. The results of the study showed that the production process of MSME entrepreneurs in Jelun village, Gumuk village, Pakel village, and Kluncing village was still very simple and capital was minimal so it was difficult to develop their businesses. In addition the procurement of raw materials is limited. As for the narrow marketing reach.